Restrukturisasi Pendidikan Menuju Bangsa Berkarakter - Mustofa Kamal (Madaniyah, 2014)
National development priorities as outlined in the National Long-Term Development Plan (RPJP) for 2005 - 2025 (Law No. 17 of 2007), among others, are in realizing a society that is noble, moral, ethical, cultured, and civilized based on the philosophy of Pancasila ". One effort to realize this is by strengthening the national identity and character through education. Character education is the most important key to the revival of the Indonesian people from adversity to welcome the arrival of a new civilization. The multidimensional crisis is a national problem. This happens because this nation is not confident in developing and conceptualizing the nation's progress. Being a nation that stands on its own feet, will restore sovereignty, be a nation that is cultured and dignified. Education that is designed is no longer education that imitates other countries. The concept of education is made based on the character of society by prioritizing the norms, values, and culture that develops.